The Powers of Rivers. Issue 2 (3rd July 2022) - Smith, Laurence C.
Abstract : Humans and rivers have shared an intimate relationship since prehistoric times. This curation uses visual representations to explore some of the many ways that humans interact with these geographical features. Through photographs, a political map, and line art, it invites the reader to consider the myriad and changing demands we impose on fluvial systems through quests for access, natural capital, territory, well-being, and power.